Current Geopolitical Processes as a Methodological Opportunity for (Literary) Imagology - Pešková, Michaela; Mišterová, Ivona (Zagadnienia Rodzajów Literackich, 2023)
The article proposes a hypothesis that traditional imagological concepts are no longer sufficient for interpreting the current and recent “imagological situation”. The authors argue that given the significant changes in the geopolitical ordering of the world in the post-imperial period, it is necessary to expand and internally categorize the terms to capture a more nuanced way of looking at the “other”. The article provides a summary of existing approaches and suggests innovations, particularly in making a careful distinction between the self-image of the internal and external, and the disaggregation of the “meta-image” into several layers. The authors point out that imagological research needs to consider that the ethnic identity of the recipient is not unambiguous, which problematizes the interrelation of “us” and “them”. Additionally, in post-imperialism, there is an unravelling of the former bipolar perception. The authors trace the image in the context of concepts such as image, stereotype, and brand. The essay aims to analyse the manifestations of the emerging neo-imperialism, which returns to the traditional contrasting delineation of “our” and “the foreign”. It also examines the factor of evaluation and the question of fictionality. The effectiveness of the new approaches is demonstrated in a Russian-Czech comparative analysis of selected novels by Vladimir Sorokin and Jáchym Topol. The authors perceive the current geopolitical processes as an opportunity for improving the imagological methodology and imagology as an effective tool for interpreting the contemporary world.